The Role of Leadership in Digital Learning Organizations - Dávid Máté Hargitai; Andrea Bencsik (Emerging Science Journal, 2023)
The study aims to examine the relationship and interaction between learning organization culture and the factors influencing digital transformation (leadership style, training, digital readiness, and trust), as well as identify factors that significantly influence learning organization functioning by exploring the extension of a grounded theory framework. The survey was conducted using an online questionnaire. The survey population was composed of managers of Eastern European manufacturing companies who were reached through the Orbis database. The survey yielded 618 evaluable responses (n = 618). The PLS-SEM method was used because the structural model is complex, with many constructs (some of which are formatively measured) and model relationships. Leadership behavior and a supportive management style inspire the development and training of employees, through which the level of readiness for digitalization and Industry 4.0 technologies can be increased. Training in these skills will increase confidence in digitalization technologies. Leadership support also influences digital trust and employee response to the use of digital technologies, as does participation in training, which directly supports digitalization and I4.0 readiness. The results of the research not only support previous research findings but also complement them by focusing specifically on the impact on the learning organization in the context of digitalization. This study provides evidence that leadership that is supportive of the learning organization's culture plays a key role. Overall, leadership is a dominant influence in the digital transformation of organizations and in shaping the learning organization culture this requires, but all the relationships represented in the model have a significant positive relationship. Doi: 10.28991/ESJ-2023-SIED2-09 Full Text: PDF